Integrating RNA Interference and Nanotechnology: A Transformative Approach in Plant Protection - Mohammad Shafiqul Islam; Md Robel Ahmed; Muhammad Noman; Zhen Zhang; Jing Wang; Ziqi Lu; Yingying Cai; Temoor Ahmed; Bin Li; Yanli Wang; Abul Khayer Mohammad Golam Sarwar; Jiaoyu Wang (Plants)
RNA interference (RNAi) has emerged as a potent mechanism for combating pathogenic fungi and oomycetes over the past decades. It offers a promising gene-silencing approach by targeting crucial genes involved in diseases caused by economically and scientifically significant fungal pathogens, such as Botrytis cinerea and Fusarium species. Simultaneously, nano-agro-products have gained attention as alternatives to traditional fungicides in plant protection strategies. However, the instability of naked RNA molecules outside the cellular environment presents a challenge, as they degrade rapidly, limiting their efficacy for prolonged disease control. Concerns regarding the toxicity of protective nanoparticles to non-target organisms have also arisen. Integrating RNAi with nano-agro-products, particularly nanocarriers, to form RNA-nano complexes has demonstrated significant potential, providing enhanced RNA stability, reduced toxicity, and extended disease control. This review explores the mechanisms of RNA-nano complexes-mediated plant protection, addressing RNA stability and nano-toxicity issues while examining the prospects of RNA-nano complex research in plant pathogen management.